Analyzing The Influence of Mappatabe' Culture on Education in The Bugis Region - Muh. Riswan; Syamsu T; Syahrir L; Nurul Faradillah; Sam Hermansyah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study aims to analyze the influence of Mappatabe' culture on education in the Bugis region, with a particular focus on Lasiwala Village, Sidrap District, South Sulawesi. Mappatabe' is a local tradition that reflects the values of respect, politeness, and morality passed down from generation to generation in Bugis society. This study used a qualitative approach with in-depth interviews, participatory observation and document analysis to collect data from various parties, including religious leaders, educators, traditional leaders and the younger generation. The results showed that Mappatabe' culture has an important role in shaping students' character, especially in terms of respect for parents, teachers, and others. The values contained in Mappatabe' also contribute to improving discipline and order in the school environment. However, the main challenge in preserving this culture is the influence of modernization and globalization which tends to reduce traditional respectful practices. In addition, the lack of in-depth understanding of the values of Mappatabe' makes most of the younger generation only see it as a formal ritual without understanding the moral essence contained in it. To maintain the sustainability of this culture in education, this research recommends collaboration between families, schools and communities in integrating Mappatabe' values into the formal and non-formal education curriculum. Strategies that can be implemented include strengthening local culture-based character education, increasing the involvement of traditional leaders in learning, and using interactive learning methods such as traditional games and folklore. This research makes an important contribution to the development of local culture based education in Indonesia, particularly in maintaining Bugis cultural identity amidst changing times. By maintaining and adapting the Mappatabe' culture, it is hoped that the younger generation can still understand and apply the ethical and moral values that characterize Bugis society.